THE PROFIT OF THE BANKING SECTOR - PhD Gafurova Azizakhon Fatixovna (American Journals, 2024)
This article discusses the principles of banking, income generation, expenses, as well as making a profit. The statistical data of the banking sector have been studied.
Keywords: Bank, profitability, income, expense, profitability coefficients, profitability indicators.